Investasi Langsung di Era Ekonomi Digital: Tantangan dan Peluang Baru dalam Kerangka Hukum - Kartika Ayu Suhanti (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Direct investment in the digital era raises a number of complex legal challenges that need to be addressed by market players and regulators. Some of these challenges include data privacy and security, intellectual property rights protection, cybercrime, and complex regulatory issues. However, amidst these challenges, there are also opportunities and innovations that can be exploited within the investment legal framework directly. One opportunity that can be explored is the establishment of regulations specifically for the digital economy. With appropriate regulations in place, the investment environment in this sector can become more conducive. Regulations should cover aspects such as data protection, cyber security, electronic commerce and technological innovation. Apart from that, changes in regulations are also key in facing the rapidly changing dynamics of the digital economy. Ease of obtaining permits, simpler investment procedures, and policies that are responsive to technological developments can encourage investment growth in the digital sector. Protection of intellectual property rights is also important in dealing with direct investment in the digital economy. Since much of the investment in this sector is related to technological development and innovation, strong protection of copyrights, patents and trademarks is essential. Cyber ​​security is also an important focus in the direct investment legal framework. The threat of cyber attacks can damage infrastructure, steal sensitive data, and harm a company's reputation. Therefore, regulations must strengthen aspects of cybersecurity, including best practices in data protection and rapid response to security incidents. Apart from that, to increase direct investment in the digital economy, increasing digital literacy among the public and business people is also important. Education and training on digital technologies and related legal aspects can help reduce barriers to investment in this sector. Finally, cooperation between the government, private sector and community institutions in developing the legal framework for direct investment is also an important factor. This collaboration can facilitate sustainable and inclusive investment in the digital economy. By paying attention to these opportunities and innovating in accordance with the applicable legal framework, Indonesia can create a more attractive investment environment for investors and accelerate the growth of the digital economic sector